Mota-Engil : equity valuation - Rocha, Sebastião Lima David Andrade (2015)
The main goal of this dissertation was to reach the price per share of Mota-Engil Group as of the 31st of December 2013. In order to achieve such goal, in a first stage, we performed a Literature Review – gathering and presenting the most commonly used methods of equity valuation. Moreover, we concluded that the Discounting Cash Flow model (more specifically the Free Cash Flow to the Firm approach) was the most appropriate to value the price of Mota-Engil’s shares. Plus, we also show the results achieved through Relative Valuation. Our target price is 9.65€ per share whereas the price practiced by the market at such date was 4.32€. Thus, according to the model by us developed, Mota-Engil’s shares were undervalued, in the end of 2013.